Detecting and developing youth athlete potential: Different strokes for different folks are warranted - Suppiah, H. T.; Low, C. Y.; Chia, M. (British Journal of Sports Medicine, 2015)
Sport talent identification and development (TI and TD) in youth continues to attract strong interest among coaches, sport scientists and sport administrators. TI for sport in youth with the anticipation of future elite level sport achievement is both an art and a science, and is strongly influenced by within athlete and extraneous-to-athlete factors (ecosystem of support or the lack of). The returns from investment on current TI and TD models of sport in youth are subpar in that few continue in the sport to achieve podium positions at the elite sport level in adulthood. Why, where and how one succeeds in sport, and what that success means to the athlete and stakeholders are dependent on the culture and context of the country. We advocate harnessing the power of sport to help in youth development, to be holistic in its nurturance, to allow for individual idiosyncratic expressions of the athletes, to provide for talent transfer across sport, and to facilitate key stakeholders to join hands to work for the common interest and understanding for as many youth and adults so as to provide them with opportunities through support and coaching to compete at the different levels of competition in sport. Governments, policy makers and administrators of sport must decide, within their specific circumstances, if TI and TD in sport in youth is serving a meaningful purpose and is a viable return on investment; in short, is it mission possible or is it quest for the Holy Grail for a podium finish in elite level sport competition? Detecting and developing youth athlete potential: Different strokes for different folks are warranted.